2011
DOI: 10.1080/17458081003774677
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of selenium and tellurium nanorods

Abstract: Selenium and tellurium nanorods were synthesised by the reaction of glucose with Na 2 SeO 3 and Na 2 TeO 3 under hydrothermal conditions. The products are characterised in detail by the multiform techniques: X-ray diffraction, energy dispersive X-ray analysis, scanning electron microscopy and transmission electron microscopy. The results show that the selenium products are nanorods with diameters of about 200-300 nm, and lengths ranging between 1 and 3 mm. The diameters of the tellurium nanorods range from 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Chemical synthesis of TeNRs is mostly reliant on the addition to the reaction system of surfactant molecules 32 34 that adsorb onto the TeNP surface limiting their aggregation 31 . Once the transition from a -Te to t -Te takes place, the formation of single-crystalline NRs is driven by the surfactant molecules that strongly interact with Te 0 atoms, confining the growth of TeNRs along one axis without affecting their diameter 30 , 31 , 35 , 36 . Since little variation in the diameter of the biogenic TeNRs was detected (Supplementary Table S2 ), this observation indicated that amphiphilic biomolecules supplied by the BCP1 cells acting as surfactants could mediate the growth of NRs along one axis.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical synthesis of TeNRs is mostly reliant on the addition to the reaction system of surfactant molecules 32 34 that adsorb onto the TeNP surface limiting their aggregation 31 . Once the transition from a -Te to t -Te takes place, the formation of single-crystalline NRs is driven by the surfactant molecules that strongly interact with Te 0 atoms, confining the growth of TeNRs along one axis without affecting their diameter 30 , 31 , 35 , 36 . Since little variation in the diameter of the biogenic TeNRs was detected (Supplementary Table S2 ), this observation indicated that amphiphilic biomolecules supplied by the BCP1 cells acting as surfactants could mediate the growth of NRs along one axis.…”
Section: Resultsmentioning
confidence: 99%
“…One approach was to synthesize Se with different morphologies and structures, such as nano-brous Se and porous Se. 12,13 Kundu et al prepared brous Se as a cathode material with a reversible capacity of 375 A h kg À1 at a rate of C/13. Another approach was to conne Se within various forms of carbon material, such as porous carbon, 8 carbon nanotubes 10 and reduced graphene oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis methods of selenium structures include photocatalytic, pulsed laser ablation, vapor deposition, hydrothermal, solvothermal, microwave-assisted, and electrochemical. These methods have been utilized in earlier works to achieve various morphologies including nanorods (Cao et al, 2011 ), nanowires (An et al, 2003 ), nanotubes (Chen and Gao, 2006 ), and butterfly-like structures (Zeng et al, 2013 ). Electrochemical deposition (or electrodeposition) uses an electric current to deposit a material onto a conducting surface by electrochemical reduction; it is a particularly attractive method as it not only is simple and cost-effective, but also allows for fine tuning of size, composition, surface structure and thus chemical and electrical properties via precise control of reaction conditions.…”
Section: Introductionmentioning
confidence: 99%